Overseas briefing. (Times Higher Education, 2008)
The article offers news briefs related to universities & colleges. The government of Japan aims to increase the number of overseas students at the country's universities to 30,000 by 2020. A student of Georgia Highlands College in the U.S. was accussed of jacking into the computer system of the college with the attempt to change his grades. Based on a survey, it was found that students in China have open attitudes towards sex.